The Role of Brand Image in Mediating the Influence of Product Quality on Repurchase Decisions of Viva Cosmetics Products (A Study on Consumers of Viva Cosmetics Lipstick in Denpasar City) - Putu Endra Widyatama; Putu Yudi Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
In the current era of globalization, there has been an increasing emergence of new manufacturers in the cosmetics industry. Competition within the personal care and cosmetics market has become more intense. In this study, the chosen cosmetics manufacturer is PT Vitapharm, a company with extensive experience in producing cosmetics. Viva Cosmetics is committed to maintaining superior quality, which is reflected in its products, as well as fostering a competitive and positive brand image in the cosmetics industry to attract consumer interest. This study aims to analyze the role of brand image in mediating the influence of product quality on the repurchase decisions of Viva Cosmetics products. The research was conducted in Denpasar City, with a sample size of 120 respondents who had previously purchased Viva Cosmetics lipstick products. The sample was obtained using a non-probability sampling method with purposive sampling technique. Data were collected by distributing online questionnaires. The data analysis method used is Structural Equation Modeling – Partial Least Squares (SEM-PLS). The results of the analysis indicate that product quality has a positive and significant influence on repurchase decisions, product quality has a positive and significant influence on brand image, brand image has a positive and significant influence on repurchase decisions, and brand image mediates the influence of product quality on repurchase decisions. Furthermore, brand image partially and complementarily mediates the relationship between product quality and repurchase intention.